PENERAPAN METODE KOMUNIKASI DALAMÂ MERUBAH PERILAKU SOSIAL UNTUK MENINGKATKAN KUNJUNGAN K4 IBU HAMIL DI KABUPATEN BANYUWANGI - Prabowo, Eko; Pupuh Satiti, Nantiya (JURNAL KEPERAWATAN BINA SEHAT, 2016)
Antenatal care(ANC) is very importantfor pregnant women. Prenatal periodisa period of preparation, both physically (fetal grow thand maternal adaptation) and psychological (anticipatedto be a parent). Butin fact, up to this time K4 visit coveragein pregnant womenin Banyuwang is till low enough ordo not meet the set targets. The purpose of this study was to investigate the application of methods of communication in changing social behavior to improve K4 visit pregnant women in Banyuwangi 2014.This study used quantitative research methods to design the expansion draft randomized control group pretest-posttest design. The independent variableis the method of communication in changing social behavior (methods of health education in health vasilitas, workshops community leaders, and educational cadres), and the dependent variablein the form of visits K4 pregnant women. Sampling technique using multi stage sampling. Location of the study are in PHC Sempu. Instruments research on variable communication methodin changing social behavioris a unit of learning program (SAP) and the variable K4 visit pregnant women using observation KIA book. Statistical testin this study is a statistical test Che-Square One Sample and Kruskal Wills.The results showedthe influence of classes and support pregnant women with ρ0:00 husband, Communication cadres with 0:00 ρ and ρ public figures with 0001. Theory Snehandu B. Karin Notoatmodjo, (2007) analyzed thestarting point of health behavior that the behavior of one of which is a function of the presen ceorab sence of information about health or medical facility (accesebility of information) and social support from the surrounding community (social support). Forthat we need the strong support both in terms of policies and toolsin order to improvethe effectiveness of reporting K4 pregnant women.Keywords: Visits K4, Behavior